Skim - Tamaki, Mariko (London : Walker Books, 2009)
Wiccan goth teen Kimberly Keiko Cameron sinks into a growing depression after her classmate's ex-boyfriend kills himself, sparking a school revolution that forces all the students to redefine themselves.
2008.
Adult
Keywords: Depression, Mental -- Comic books, strips, etc -- Fiction; Friendship -- Comic books, strips, etc -- Fiction; Teenagers -- Comic books, strips, etc -- Fiction; Wiccans -- Comic books, strips, etc -- Fiction; Comic books, strips, etc; Depression (Psychology) -- Comic books, strips, etc -- Fiction; Friendship -- Comic books, strips, etc -- Fiction; Graphic novels; Teenagers -- Comic books, strips, etc -- Fiction; Wiccans -- Comic books, strips, etc -- Fiction; Graphic novels